Culturally Adapted and Digital Media Interventions for HIV Prevention: A Narrative Review - Arwan (Yayasan Sinergi Kawula Muda, 2023)
HIV/AIDS prevention campaigns rely on effective communication strategies to enhance public awareness, promote behavioral change, and increase healthcare accessibility. This study examines the impact of culturally tailored interventions, digital media campaigns, and school-based education in advancing HIV prevention efforts. A systematic literature review was conducted using multiple academic databases, focusing on peer-reviewed studies that analyze the effectiveness of health messaging in diverse socio-cultural contexts. Findings reveal that culturally resonant communication strategies significantly improve engagement and reduce stigma, particularly among marginalized populations. Digital media interventions, including social media campaigns and mobile health applications, enhance outreach and increase HIV testing and preventive behaviors. School-based and peer-led educational programs reinforce knowledge retention and foster positive attitudes toward HIV prevention. However, systemic barriers such as economic disparities, stigma, and healthcare accessibility continue to challenge the effectiveness of communication campaigns. To address these challenges, policy interventions must focus on integrating culturally relevant messaging, expanding digital health resources, and strengthening multi-sector collaborations. Future research should explore innovative digital health solutions and longitudinal assessments of communication strategies to enhance their efficacy. By incorporating these elements, HIV prevention campaigns can achieve greater inclusivity and effectiveness in reducing transmission rates and improving public health outcomes.